Factors Affecting The Decision Using Theory Of Planned Behavior (Case Study: Election Of The 2019 President) - Zahra, Akmalia; M. Munandar, Jono; Sarma, Ma’mun (Jurnal Indonesia Sosial Sains, 2022)
Indonesia has adopted a democratic system since the 1998 reform era which includes many aspects, including politics. The Indonesian people are the highest authoritys holder who are entitled to the opportunity and voice in regulating government policies. With different racial, religious, ethnic backgrounds, it is hoped that all indonesians citizen can participate in this election. Although the distribution of the Indonesian population is concentrated in Java, it does not make the focus of political marketing only on Java. There are restrictions on age, education, geographical or socio-economic in political marketing, then the right marketing strategy is needed. Political actors need to know the characteristics and behavior of voters to determine an effective communication strategy. The purpose of this study is to analyze the factors that influence decisions outside of Java using Theory of Planned Behavior. Data were processed using SEM analysis with AMOS 23.0. The results showed that the factors that influence the intention to vote outside of Java are attitudes and subjective norms. 10% of the total respondents stated that they had not made a choice when the questionnaires were distributed, so there is a possibility that swing voters will determine the votes in the last seconds of the election.